Coefficients of modified broyden method and its global convergence - Mohd Asrul Hery Ibrahim; Zahratul Amani Zakaria; Mustafa Mamat; Azfi Zaidi Mohammad Sofi (Pushpa Publishing House, 2016)
In this article, a new search direction for the Broyden family method is proposed for solving unconstrained optimization problems. The new search direction is developed by using the search direction of conjugate gradient method approach. This method is popular as M-Broyden method. The suggested method has an attractive property that its search direction is sufficiently descent in every iteration. Under mild conditions, we prove that the proposed method has global convergence.